Effects of Land Use Changes on Streamflow and Sediment Yield in Atibaia River Basin-SP, Brazil - Mendonca dos Santos, Franciane; Proenca de Oliveira, Rodrigo; Augusto Di Lollo, Jose [UNESP] (Mdpi, 2020)
The Soil and Water Assessment Tool (SWAT) is often used to evaluate the impacts of different land use scenarios on streamflow and sediment yield, but there is a need for some clear recommendations on how to select the parameter set that defines a given land use scenario and on what is the most appropriate methodology to change the selected parameters when describing possible future conditions. This paper reviews the SWAT formulation to identify the parameters that depend on the land use, performs a sensitivity analysis to determine the ones with larger impacts on the model results and discusses ways to consider future land use conditions. The case study is the Atibaia river basin, with 2838 km(2)(Sao Paulo, Brazil). The parameters identified by sensitivity analysis with the largest impacts on streamflow and sediment yield were the initial curve number for moisture condition II (CN), maximum canopy storage for each land use (CANMX) and the cover and management factor (USLE_C). The identification and appropriate parameter change can provide real estimates of the magnitudes in the land use changes, which were verified in this study. Such information can be used as an instrument for proposing improvements in the basin's environmental quality and management.
Keywords: SWAT; scenarios; land use; river basin